Apoptotic effect of Aralia echinocaulis extract on fibroblast-like synoviocytes in rats with adjuvant-induced arthritis via inhibiting the Akt/Hif-1α signaling pathway in vitro - Yunzhi Li; Ning He; Liqun Shen; Mingdong Liu (Elsevier, 2019)
Aralia echinocaulis is used for the treatment of rheumatoid arthritis by Tujia Minority in China. A previous study demonstrated that A. echinocaulis had a significant anti-arthritic effect on adjuvant arthritis (AA) rats in vivo. However, it remains unclear whether A. echinocaulis can induce the apoptosis of fibroblast-like synoviocytes (FLS) from AA rats and the underlying mechanism is unknown. In this paper, CCK-8 assay, Hoechst staining and flow cytometry were used to evaluate the apoptotic effect of an A. echinocaulis ethanol extract (AEE) on AA FLS. Western blotting analysis was performed to measure the protein expression levels of Bcl-2, Bax, cleaved caspase-3, Akt, p-Akt, and Hif-1α. The results revealed that AEE could inhibit FLS proliferation in a dose and time-dependent manner. After treatment with AEE, AA FLS displayed the classical apoptotic morphology, and the apoptosis rates were significantly increased. Furthermore, we found that AEE increased the protein levels of Bax, cleaved caspase 3, and decreased the protein levels of Bcl-2, Hif-1α and p-Akt, without affecting total Akt levels. Collectively, these results suggested that the apoptosis inducing effect of AEE on AA FLS was related to the regulation of the expression of apoptosis-related proteins and the inhibition of the Akt/Hif-1α signaling pathway. Keywords: A. echinocaulis, Apoptosis, Akt/Hif-1α signaling pathway, Fibroblast-like synoviocyte, Rheumatoid arthritis